Bioengineering of a scaffold-less three-dimensional tissue using net mould. (17th September 2021) - Sakaguchi, Katsuhisa; Tobe, Yusuke; Yang, Jiayue; Tanaka, Ryu-ichiro; Yamanaka, Kumiko; Ono, Jiro; Shimizu, Tatsuya
Abstract: Tissue engineering has attracted attention worldwide because of its application in regenerative medicine, drug screening, and cultured meat. Numerous biofabrication techniques for producing tissues have been developed, including various scaffold and printing methods. Here, we have proposed a novel tissue engineering method using a net metal mould without the use of a scaffold. Briefly, normal human dermal fibroblasts seeded on a dimple plate were subjected to static culture technique for several days to form spheroids. Spheroids of diameter ⩾200 μ m were poured into a net-shaped mould of gap ⩽100 μ m and subjected to shake-cultivation for several weeks, facilitating their fusion to form a three-dimensional (3D) tissue. Through this study, we successfully constructed a scaffold-free 3D tissue having strength that can be easily manipulated, which was difficult to construct using conventional tissue engineering methods. We also investigated the viability of the 3D tissue and found that the condition of the tissues was completely different depending on the culture media used. Collectively, this method allows scaffold-free culture of 3D tissues of unprecedented thickness, and may contribute largely to next-generation tissue engineering products.